A Phase 2 randomized, observer-blind, placebo-controlled, dose-ranging trial of aluminum-adjuvanted respiratory syncytial virus F particle vaccine formulations in healthy women of childbearing age. Issue 30 (27th June 2017) - August, Allison; Glenn, Gregory M.; Kpamegan, Eloi; Hickman, Somia P.; Jani, Dewal; Lu, Hanxin; Thomas, D. Nigel; Wen, Judy; Piedra, Pedro A.; Fries, Louis F.
Abstract: Objective: Respiratory syncytial virus (RSV) causes significant morbidity and mortality in infants. We are developing an RSV fusion (F) protein nanoparticle vaccine for immunization of third trimester pregnant women to passively protect infants through transfer of RSV-specific maternal antibodies. The present trial was performed to assess the immunogenicity and safety of several formulations of RSV F vaccine in 1-dose or 2-dose schedules. Methods: Placebo, or vaccine with 60 μg or 120 μg RSV F protein and 0.2, 0.4, or 0.8 mg aluminum, were administered intramuscularly on Days 0 and 28 to healthy women 18–35 years old. Immunogenicity was assessed from Days 0 through 91 based on anti-F IgG and palivizumab-competitive antibody (PCA) by ELISA, and RSV A and B neutralizing antibodies by microneutralization (MN) assay. Solicited adverse events were collected through Day 7 and unsolicited adverse events through Day 91. Results: All formulations were well-tolerated, with no treatment-related serious adverse events. Anti-F IgG and PCA responses were correlated and increased after both doses, while MN increased significantly only after the first dose, then plateaued. The timeliest and most robust antibody responses followed one dose of 120 μg RSV F protein and 0.4 mg aluminum, but persistence through 91 days was modestly (∼25%) superior following two doses of 60 μg RSV F protein and 0.8 mg aluminum. Western blot analysis showed RSV infections in active vaccinees were reduced by 52% overall (p = 0.009 overall) over the Day 0 through 90 period. Conclusions: RSV F nanoparticle vaccine formulations were well tolerated and immunogenic. The optimal combination of convenience and rapid response for immunization in the third trimester occurred with 120 μg RSV F and 0.4 mg aluminum, which achieved peak immune responses in 14 days and sufficient persistence through 91 days to allow for passive transfer of IgG antibodies to the fetus.NCT01960686 .